Alterações nos atributos microbiológicos do solo e nos estoques de carbono decorrentes do cultivo de eucalipto no Bioma Pampa - Moraes, Júlia Rodegheiro de (2012)
In southerm Rio Grande do Sul State, Brazil, cultivation of eucalyptus forests have been growed in the last few years, raising questions about possible impacts on local biome, characterized by herbaceous and shrub vegetation. This study aimed to evaluate soil microbial and carbon stocks changes due to eucalyptus cultivation in Pampa Biome. The evaluated soils were: Udalfs and Typic Udorthents derived from igneous plutonic rocks (granites), Lithic Udorthents derived from metamorphic rocks (schists and quartzites), and Udolls/Uderts derived from sedimentary rocks (shales and siltstones). Vegetation covers were homogeneous Eucaliptus saligna (7 years old) and native grassland. In each area three soil pits were opened with no less than 50cm deep. Pedogenetic horizons were identified and soil morphology was described. Disturbed and non disturbed soil samples were collected, the A horizon in 5cm intervals. Chemical attributes (exchangeable cations, potential acidity, water and SMP pH, total organic carbon and nitrogen) and physical attributes (particle size and coarse fractions) were determined for classification purposes. Soil bulk density was determined for soil profile carbon stocks calculation. In the 0-5, 5-10 and 10-15cm A horizon layers, the organic matter granulometric fractionation was performed for quantification of carbon and nitrogen in labile (POC and PN) and mineral associated (MOC and MN) fractions, as well as carbon management index (CMI). In the 0-5 and 5-10cm layers soil microbial biomass, microbial C (Cmic) and microbial N (Nmic), soil basal respiration, metabolic coefficient, and Cmic/TOC, Nmic/TN, Cmic/Nmic rates were determined. Compared to the native grassland, the seven years cultivation of eucalyptus did not modify soil carbon stocks of the profiles. Carbon stocks decrease in order Udolls/Uderts > Lithic Udorthents > Udalfs = Typic Udorthents. Labile fraction stocks (POC and PN) of the Udolls/Uderts were increased in the 0-5 and 5-10cm layers. Mineral associated fractions (MOC and MN) remained unaltered in all soils. TOC and TN distribution in the labile (POC/TOC and PN/TN) and stable (MON/TOC and MN/TN) fractions were modified only in the 5-10cm layer of the Udolls/Uderts. Carbon management indexes, except in Lithic Udorthents, indicate that eucalyptus cultivation did not decrease the organic matter quality and stocks in the soils. Soil microbial activity and biomass were not altered in comparison to the native grassland, with the exception of microbial carbon in the 5-10cm layer of the Typic Udorthents.